2008
DOI: 10.1111/j.1095-8312.2008.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific offspring killing in owls

Abstract: In Baranya County (Southern Hungary), tawny owls (Strix aluco) and barn owls (Tyto alba) sequentially use the same nest boxes in a significant number of cases. A total of 460 broods were observed between 1996 and 2003 and, in 12 cases, whole broods of dead tawny owl chicks were registered that had apparently been killed. On investigating the reproductive life characteristics, population sizes, and frequency of killing in these two species, it was concluded that: (1) with growing barn owl population, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Cases of infanticide between these two wren species were almost certainly based on food resource competition, since nestlings were killed only during a pronounced food shortage. Barn owls ( Tyto alba ) have been reported to increase their reproductive success by killing the broods of tawny owls ( Strix aluco ) in times of breeding place shortage (Mátics et al, 2008 ). The underlying causes of interspecific infanticide are still poorly understood, as the key adaptive hypothesis proposed to explain conspecific infanticide [e.g., the “sexual selection” hypothesis: Hrdy, 1979 ; van Schaik, 2000 ] cannot be applied to cases of interspecific infant killing.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of infanticide between these two wren species were almost certainly based on food resource competition, since nestlings were killed only during a pronounced food shortage. Barn owls ( Tyto alba ) have been reported to increase their reproductive success by killing the broods of tawny owls ( Strix aluco ) in times of breeding place shortage (Mátics et al, 2008 ). The underlying causes of interspecific infanticide are still poorly understood, as the key adaptive hypothesis proposed to explain conspecific infanticide [e.g., the “sexual selection” hypothesis: Hrdy, 1979 ; van Schaik, 2000 ] cannot be applied to cases of interspecific infant killing.…”
Section: Introductionmentioning
confidence: 99%
“…Barn Owls can disrupt nests of the smaller species by destroying clutches, killing the young (Mátics et al 2008), or even killing the adults (Génot and Nieuwehuyse 2002;Roulin 2002;Charter et al 2007a). …”
Section: Introductionmentioning
confidence: 99%
“…Although the earlier studies demonstrated that the application of nest boxes increased the clutch size and breeding success compared to natural nesting sites (Marti et al 1979, Johnson 1994, the advantages of nest boxes were questioned by a Hungarian study, which showed that the survival of owls differed between the artificial nest box and the 'natural' environment of a church tower (Klein et al 2007). Moreover, in the case of the artificial nest box application, more species could occupy the same nest boxes which realise competitive situation or predation (Charter et al 2010a) such as the interspecific offspring killing which was reported in the interaction between Tawny Owl (Strix aluco) and Common Barn-owl (Mátics et al 2008).…”
Section: Introductionmentioning
confidence: 99%